To divide or not to divide: An alternative behavior for teratocytes in Encarsia pergandiella (Hymenoptera: Aphelinidae). Issue 1 (January 2016) - Mancini, Donato; Garonna, Antonio P.; Pedata, Paolo A.
Abstract: Encarsia pergandiella (Hymenoptera: Aphelinidae) is an endoparasitoid with an unusual embryonic development compared to most of congeneric species and all other members of the superfamily Chalcidoidea. The developmental background of this wasp is based on an alecithal hydropic egg, with the embryo developing inside an extra-embryonic membrane which dissociates at hatching into special larva-assisting cells, the teratocytes. In E . pergandiella many teratocytes at hatching were multinucleated syncytial cells with no evidence of a cellular membrane separating the nuclei. These teratocytes during larval development produced smaller uninucleated teratocytes, through successive divisions obtained by progressive ingrowth of the plasmatic membrane, accompanied by appearance of degeneration symptoms, such as protrusions and blebs . As a consequence of this divisional process teratocytes showed a size reduction and an increase in number of about four times during the second day of larval development. Only on the third day of larval life teratocytes started to decrease in number, until total disappearance at larval maturation. This behaviour is in striking contrast with all other studied systems in which teratocytes do not divide and progressively decrease in number as the parasitoid larva develops. Highlights: We investigated the cytology and life history of teratocytes of Encarsia pergandiella . Teratocytes have at hatching a wide size range. Teratocytes present a variable number of nuclei related to size. Multinucleated teratocytes divide during larval development into smaller and uninucleated ones. We demonstrated that in these species teratocytes exhibit unique developmental features.